Impacts of alkaline on the defects property and crystallization kinetics in perovskite solar cells - Yihua Chen (Nature Portfolio, 2019)
Defect density reduction is pertinent for halide perovskite solar cells but a universal strategy has not been exploited. Here Chen et al. show that by fine tuning the alkaline environment in precursor solution, they can greatly suppress defects density and obtain high certified efficiency of 20.87%.